Religion after Kant: God and culture in the idealist era - Bubbio, Paolo Diego; Redding, Paul (Cambridge Scholars, 2012)
Kantian origins : one possible path from Transcendental Idealism to a "Post Kantian" philosophical theology / Paul Redding -- The volcano and the dream : consequences of Romanticism / Robert Sinnerbrink -- Hegel as an interpreter of religious experience / Maurizio Pagano -- Hegel's incarnationalism / Damion Buterin -- Schelling's Berlin lectures / Wayne Hudson -- Feuerbach's philosophical psychology and its political and aesthetic implications / Jean-Philippe Deranty -- Kierkegaard is standing by himself -- through Hegel's help : the notion of sacrifice in Kierkegaard's Works of love / Paolo Diego Bubbio -- Nietzsche's new religion / Julian Young